In-patient outcomes of patients with diabetic ketoacidosis and concurrent protein energy malnutrition: A national database study from 2016 to 2017. Issue 8 (17th November 2021) - Kichloo, Asim; Shaka, Hafeez; El-Amir, Zain; Wani, Farah; Singh, Jagmeet; Velazquez, Genaro Romario; Edigin, Ehizogie; Dahiya, Dushyant
ABSTRACT: Introduction: Patients often present to the hospital with a well-known complication of diabetes mellitus, namely diabetic ketoacidosis (DKA). In this study, we assess the clinical outcomes of DKA hospitalizations with and without protein-energy malnutrition (PEM). Methods: This was a population-based, retrospective observational study using data gathered from the Nationwide Inpatient Sample (NIS) for 2016 and 2017. Hospitalizations of adults >/ = 18 years old with a principal diagnosis of DKA were obtained using ICD-10 codes and divided into groups based on a secondary diagnosis of PEM. The primary outcome was in-hospital mortality. Secondary outcomes included length of stay (LOS), total hospital charges (THC), and system-based complications. Results: Patients with PEM had a statistically significant difference in the adjusted odds for in-hospital mortality compared to patients without PEM (aOR 1.73, 95% CI: 1.20–2.49, p = 0.004). Patients with DKA and PEM had an increased risk of developing sepsis (aOR 2.99, 95% CI: 2.49–3.58, p < 0.001), septic shock (aOR 3.37, 95% CI: 2.31–4.91, p < 0.001), acute kidney failure (aOR 1.27, 95% CI: 1.17–1.37, p < 0.001), acute respiratory failure (aOR 2.23, 95% CI: 1.83–2.73, p < 0.001), deep vein thrombosis (aOR 1.91, 95% CI: 1.43–2.54, p < 0.001), and pulmonary embolism (aOR 2.36, 95% CI: 1.42–3.94, p = 0.001). Patients with DKA and PEM also had an increased mean THC (aOR 19, 200, 95% CI 16, 000–22, 400, p < 0.001) in US dollars and increased LOS (aOR 2.26, 95% CI 1.96–2.57, p < 0.001) in days when compared to patients without PEM. Conclusion: Patients hospitalized for DKA with a secondary diagnosis of PEM within the same admission had a statistically significantly higher in-hospital mortality.